Collimation and Image Quality of C-Arm Computed Tomography. Issue 8 (August 2015) - Werncke, Thomas; von Falck, Christian; Luepke, Matthias; Stamm, Georg; Wacker, Frank K.; Meyer, Bernhard Christian
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to assess the potential for radiation dose reduction in collimated C-arm computed tomography (CACT) while maintaining the image quality of the full field of view (FFOV) acquisition. Material and Methods A whole-body anthropomorphic phantom representing a 70-kg male was used in this study. The upper abdomen of the phantom was imaged using an angiographic system (Artis Zeego Q; Siemens Healthcare, Germany) with either the standard detector radiation dose level (RDL; D100, 360 nGy) or 14 experimental reduced RDLs ranging from 95% (D95, 342 nGy) to 30% D100 (D30, 108 nGy). Either the FFOV (craniocaudal coverage, 18 cm) or a collimated field of view (CFOV; craniocaudal coverage, 6 cm) was applied. The organ dose was measured using thermoluminescence detector dosimetry, and the mean effective dose was computed according to the recommendations by the International Commission on Radiological Protection Publication 103. To compare the CFOV and the FFOV data sets, image quality was assessed in terms of high- and low-contrast resolution by calculating the modulation transfer function using the wire method as well as the image noise, signal-to-noise ratio, and contrast-to-noise ratio using a low-contrast insert placed in the upper abdomen (Δ50 HU). Results Collimated imaging (CFOV) covering 33% of the FFOV led to an increase in the x-ray tube output of 152% for CFOV (D100; FFOV, 95.5 mGy; CFOV, 147.7 mGy) to maintain the detector dose. The mean effective dose of D100 was 6.0 mSv (male) and 6.2 mSv (female) for the FFOV and 3.7 mSv (male) and 4.1 mSv (female) for the CFOV. High-contrast resolution was comparable for all acquisition protocols (mean 10% modulation transfer function ± 95% confidence interval; FFOV, 8.8 ± 0.1 line pairs/cm; CFOV, 8.8 ± 0.1 line pairs/cm). Low-contrast resolution was superior for the CFOV compared with that for the FFOV for each RDL (D100; image noise: FFOV, 34 ± 2 HU; CFOV, 22 ± 1 HU; contrast-to-noise ratio: FFOV, 1.3 ± 0.2; CFOV, 1.8 ± 0.3). Low-contrast resolution of the standard (D100) FFOV acquisition was achieved for the CFOV at 84% D100 of the FFOV and 54% D100 of the CFOV. Therefore, collimation up to 33% of the FFOV combined with the lower detector dose allows overall reduction of a patient's radiation exposure to 33% × 84% = 28% compared with FFOV acquisition. In the upper abdomen, this results in a nearly 50% reduction of the mean effective radiation dose (male, 2.0 mSv; female, 2.2 mSv) without loss of image quality compared with the standard FFOV acquisition. Conclusions Craniocaudal collimation in CACT should be used whenever possible to increase the image quality and reduce the patient's overall radiation exposure. Therefore, new smart acquisition protocols are required for collimated CACT to improve the trade-off between radiation exposure and image quality requirements considering the collimation used.